Pengaruh Management Control Systems dan Organization Performance terhadap Competitive Advantage Hotel di Surabaya - Albert Susanto; Christoforus Diaz; Devie Devie; Hendri Kwistianus (Business Accounting Review, 2021)
This study aims to determine the effect of management control systems and organization performanceon competitive advantage in hotels in the city of Surabaya. In this study using the unit of analysis of 50 hotelsfrom 3 to 5 stars in the city of Surabaya by distributing questionnaires to 67 respondents, namely hotelemployees with minimum criteria of having worked for 1 year. The data obtained were then processed usingdata analysis techniques with the PLS model. The results show that management control systems have apositive effect on competitive advantage. The higher the company's management control system, the morecompetitive advantage will be in the company. The results of this study also indicate that the managementcontrol system has a positive effect on organizational performance. In this study also found that organizationalperformance has a positive effect on competitive advantage.